Potential Anthelmintic Activity of Pineapple Fruit (Ananas comosus) and Mango Leaves Juice (Mango foliorum) against Ascaridia galli Worms In-Vitro Model - Rahminiwati, Min; Martha Arofa Dilla; Nisa Najwa Rokhmah (Universitas Airlangga, 2025)
Ascaridia galli is a worm that infects the chickens' digestive tract, leading to various problems such as worsening feed efficiency, slowing poultry growth, and increasing mortality. Mango leaves and pineapple fruit were reported to have anthelmintic activity against A. galli. These two plants contain secondary metabolites that were suggested to have synergistic effects. This study aimed to determine the potential activity of combining arumanis mango leaf and pineapple juice against A. galli and evaluate their interaction based on anthelmintic activity profile. The activity of 40% pineapple fruit juice (PA) added with different concentrations of arumanis mango leaf juice (AM) from 0.13%, 0.26%, and 0.52% v/v, and pineapple fruit juice at concentrations 20, 40% v/v were mixed with 0.26% arumanis mango leaf juice. as well as NaCl 0,9% as negative control and pyrantel pamoate 0.2; 0.4; 0.8 % b/v as a positive control respectively were determined. Observation on worm mortality was conducted in 15-minute intervals for 300 minutes. The time-a cumulative mortality rate of worm curve exposed to PA 40 % was shifted to the left in the presence of AM, and AM 0.26 % curve in the presence of PA. The best, LC50, LT50, and L100 were found in AM 0.52 % combined with PA 40%. This finding showed the potential activity of pineapple fruit juice at 40% combined with arumanis mango leaf juice at 0.52 % as the best combination in which anthelmintic activity occurs due to synergism interaction between arumanis mango leaf juice and pineapple fruit juice.